Effect of spraying seaweed extract on the yield of different varieties of potatoes (Solanum tuberosum L.) - Ibrahim, Ammar Jabbar Khalaf; AL- Hamdani, Sabeeh abdulwhab (Journal of agricultural, environmental and veterinary sciences, 2018)
The experiment was conducted during the 2017 spring season planting in Baquba nursery of Diyala Agriculture Directorate- Diyala Governorate. The study included three varieties of potatoes (AXENIA, OSIRIS and HERMES), sprayed four concentrations of seaweed extract (APPETIZER) (0, 0.75, 1.50 and 2.25 ml.l-1water), with three sprays. In order to study the effect of the variety and the concentration of seaweed extract in the growth and yield of potatoes. The trial included 12 treatments resulting from the combination of the study factors above mentioned. applied Randomized complete Block Design (R.C.B.D) With three replicates, were statistical analysis using a program (SAS) The averages were compared using the Dunkin multiple rang test at 5% . The results showed that OSIRIS variety gave significantly in the total number of tubers per plant (tuber. Plant-1), tuber yield per plant (kg), Marketable yield of tubers(ton.donum-1), unmarketable yield of tubers(ton.donum-1), Total tuber yield (ton.donum-1), While AXENIA significantly the average wight of tuber marketable(gm.tuber-1). The spray seaweed extract at a concentration of 1.50 ml. l-1 was significantly in most of the studied traits, addition to a significant in the treatments of overlap between the study factors.
Keywords: potatoes; varieties; seaweed extrac